2017
DOI: 10.1007/s10643-017-0877-3
|View full text |Cite
|
Sign up to set email alerts
|

A Quasi-Experiment Examining Expressive and Receptive Vocabulary Knowledge of Preschool Head Start Children Using Mobile Media Apps

Abstract: The American Academy of Pediatrics (1999, 2011) recommends no screen time for children under two years and limited screen time for three-and four-year-olds. Despite these recommendations, most young children have easy access to various types of screens. In particular, children's use of mobile media, including tablets and other touch screen devices, is increasing (Common Sense Media, 2013). Even though scholars have highlighted positive uses for mobile media (Christakis, 2014; Radesky, Schumacher, & Zuckerman, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 42 publications
0
19
0
Order By: Relevance
“…Specifically, in 3 studies (2 RCTs), researchers examined alphabet knowledge and phonological awareness after children used apps targeting these skills, compared with apps not targeting these skills. No significant differences in learning were found between groups for 2 studies, 44,53 whereas the other found children's phonological awareness and vocabulary skills improved more after using a phonological awareness app compared with a vocabulary app. 48 In 5 studies (2 RCTs), researchers found that children's letter naming and writing skills 50,60,77,78 and phonological awareness 46,60,78 improved after using a set of LA apps compared with a classroom or in-person instruction control group.…”
Section: La Learningmentioning
confidence: 80%
“…Specifically, in 3 studies (2 RCTs), researchers examined alphabet knowledge and phonological awareness after children used apps targeting these skills, compared with apps not targeting these skills. No significant differences in learning were found between groups for 2 studies, 44,53 whereas the other found children's phonological awareness and vocabulary skills improved more after using a phonological awareness app compared with a vocabulary app. 48 In 5 studies (2 RCTs), researchers found that children's letter naming and writing skills 50,60,77,78 and phonological awareness 46,60,78 improved after using a set of LA apps compared with a classroom or in-person instruction control group.…”
Section: La Learningmentioning
confidence: 80%
“…A positive relationship was found between use of the touchscreen and the attainment of fine motor skills. Tomopoulos, S., Valdez, PT, Dreyer, BP, Fierman, AH, Berkule, SB, Kuhn, M., & Mendelsohn, AL ( 2007 ) 70 3 to 5 years Multiple Regression Cognition USA Increased exposure to non-educational content for children leads to less time for teaching and reading activities at home, which can negatively influence development. …”
Section: Resultsmentioning
confidence: 99%
“…This practice is common by parents who believe in the benefits of technology use (Guedes et al, 2020 ). Vatalaro et al ( 2018 ) demonstrated the benefits of using a scaffolding-like vocabulary application rather than any open-ended vocabulary application. Taylor et al ( 2018 ) suggest that teaching and reading activities act as a beneficial agent for learning.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lee & Cherner, ) or evaluating iOS apps in terms of diversity and multiculturalism (Cherner & Fegely, ). Specifically, some vocabulary apps were evaluated to identify their effect on young children's vocabulary acquisition (Vatalaro, Culp, Hahs‐Vaughn, & Barnes, ; Walter‐Laager et al., ) and with English as a foreign language students (Guaqueta & Castro‐Garces, ). Not much attention has been focused on vocabulary instruction apps for elementary or middle school students.…”
mentioning
confidence: 99%